Prevalence and associated factors of acute respiratory infections among children aged 1-5 years residing in district Amritsar - Lokesh, Lokesh K.; Mahajan, Sanjeev; Padda, Preeti; Kaur, Jasleen; Jyoti, Kamal (International Journal Of Community Medicine And Public Health, 2024)
Background: Acute respiratory infections (ARI) are one of the commonest causes of deaths in children in developing countries. They are responsible for the estimated 15 million deaths that occur in children under 5 years of age each year. Lower respiratory tract infections (LRTIs) are the leading cause of under-five morbidity globally. Methods: The present cross-sectional study was conducted in rural and urban areas of the Amritsar district from 01 January 2023 to 31 December 2023 among children aged 1–5 years. A total of 430 study participants, aged between 1-5 years, were included in the sample, with equal urban-rural representation (215 each). Results: The prevalence of acute respiratory tract infections in last 3 months was found to be 18% with no urban rural difference. ARI was associated with supplementary feeding and skipping meals. Conclusions: The prevalence of acute respiratory tract infections in last 3 months was found to be 18%.